Anatomi Dan Profil Metabolit Sekunder Daun Kecubung (Datura metel L.) Setelah Mendapat Perlakuan Logam Berat Tembaga - , RETYAN ANGGRIYAMURTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Copper is a heavy metal that is toxic to the environment when present in excessive amounts. Plants are the organisms that are sensitive to environmental changes. Datura is a plant that has a high tolerance to heavy metals and can produce secondary metabolites when stress caused by heavy metals. The purpose of this research is to study the anatomical structure of the leaf D.metel and secondary metabolites produced after exposure to heavy metals. In this study, Datura seedling were treated with CuSO4.5H2O solution with doses of 100, 1000, 2000, and 2500 ppm for the duration of 12, 36, 84, 132 hours. Leaf anatomical observation were done with paraffin method and used GC-MS for the analysis metabolite secondary profile. The result showed the leaves were treated with doses 2500 mg/kg of medium (132 hours) was damaged. Secondary metabolites produced in this study include beta elemene, gamma elemene, isocericenine, naphthalenone, germacrene B, and curdione. There is no addition of a new secondary metabolites in each treatment, but there are differences in total area. The concentrations of treatment doses 2500 ppm described by the highest area on several secondary metabolites produced compared with controls and other treatments as a form of self defense against stress. This result showed that D.metel can still tolerant of heavy metal with a doses less than 2500 ppm.